Study of short cracks under biaxial fatigue - López-Crespo, Pablo; Moreno-Morales, María Belén; López-Moreno, A.; García-González, Antonio Luis; Zapatero-Arenzana, José Arturo (IGF, 2014)
In this paper a methodology for evaluating crack initiation under biaxial conditions is presented. The methodology consists of evaluating the crack length automatically with digital processing of highmagnification images of the crack. The methodology was applied to study five different strain conditions on a low carbon ferritic-pearlitic steel specimen with tubular shape. A hole of 150 μm diameter was drilled to enforce the crack to initiate at a particular spot. Different combinations of axial and torsional strains were analysed during the initiation stage of the crack. The setup employed allowed detection of the crack to within 6 μm from the edge of the hole on average and monitoring of the crack during early stages. Fatigue crack propagation curves clearly showed oscillations due to microstructure. It was also observed that these oscillations decreased as the torsional component of the strain was increased.
Keywords: Materiales - Fatiga; Biaxial fatigue; Proportional loading; Fatigue crack growth; Crack initiation